The history of the development of Russian cultural volunteering: historical and contemporary practices - N I, GorlovÐ°; Z A, Troska; Ye. Z, Karpenko; Ye. V., Krutitskaya; N O, Min'kova; O V, Semin (International Journal of Engineering and Technology, 2018)
The article presents a modern methodology for organizing the practical work of volunteers in the cultural sphere using the example of Russian cultural institutions. The used methodology allows to gain knowledge and practical experience of interaction with the target audience of cultural events, to explain the main features and principles of the volunteer movement in the sphere of culture; to use successful practices of organizing the volunteers' work in cultural institutions. Using surveys, interviews and personal conversations with active participants of the research and ongoing progress of developing cultural volunteering in Russia, it allowed to supplement the material received from various sources, which significantly increased the scientific quality of author's research. In addition, the article provides an analysis of research in personal characteristics of volunteers, a system of motivation and incentives and also identifies key areas of activity. Such approach in volunteer management is complex and universal, and therefore can be used with volunteers by various cultural institutions. The practical significance of the research is that its conclusions and recommendations can be successfully used in the recruiting, professional selection and support in training, retraining and analysis of volunteer activities in the field of culture.Â Â